Persepsi pengguna terhadap pemahaman aplikasi Turnitin untuk mencegah plagiarisme pada Prodi Ilmu Perpustakaan dan Informasi Islam angkatan 2019/2020 - Witanti, Putri Triya Mei; Handayani, Nurul Setyawati (Librarium: Library and Information Science Journal, 2024)
Introduction: One of the developments in the era of technology and communication is daily access, for example the internet, which is useful for being able to search for information and provide it to other people. The large amount of incoming information can cause many works to be plagiarized, and one way to prevent this is to use the Turnitin application. The aim of this research is to find out how users perceive the understanding of the Turnitin application to prevent plagiarism in Islamic library and information science research programs. Data Collection Methods: This research uses quantitative descriptive research. Respondents were taken from Islamic Library and Information Science students for the 2019/2020 academic year, totaling 123 students, with a sample size of 55 respondents calculated using the Slovin formula. Data was collected using a questionnaire distributed via Google Form and measured using a Likert scale. Data Analysis: Data analysis uses (1) Variable description analysis, (2) Normality test with the Kolmogrov Smirnov formula to see whether the data is normal or not, (3) Linearity test with a significance value of Deviation from linearity >0.05 then linear, (4) Linear regression test to ensure the relationship between variables x and y. Results and Discussion: The research results show that students' perceptions of the cognitive aspect have the highest index value, while the aspect that needs to be improved is the affection aspect. Student understanding comes from externally. For the simple linear regression test requirements, the data must be valid, reliable, normal and linear, therefore by using a simple linear regression analysis test you can look for relationships to obtain a correlation/relationship value (R) of 0.415. The determinant coefficient (R Square) value obtained through SPSS data processing is 0.172, indicating that the independent variable (perception) has an influence of 17.2% on the dependent variable (understanding). Conclusion: Libraries need to hold workshops on plagiarism or Turnitin to check word similarities to identify plagiarism in final assignments and articles. The target is the entire academic community (lecturers, staff, and students). Therefore, it is hoped that these findings can become the basis for further research and can be continued.